2022
DOI: 10.1111/ctr.14658
|View full text |Cite
|
Sign up to set email alerts
|

The volume‐outcomes relationship in donation after circulatory death liver transplantation

Abstract: Background Donation after circulatory death (DCD) liver transplantation (LT) has become an effective mechanism for expanding the donor pool and decreasing waitlist mortality. However, it is unclear if low‐volume DCD centers can achieve comparable outcomes to high‐volume centers. Methods From 2011 to 2019 utilizing the United Network for Organ Sharing (UNOS) database, liver transplant centers were categorized into tertiles based on their annual volume of DCD LTs. Donor selection, recipient selection, and surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…A recent analysis using UNOS data from 2011 to 2019 by Delman et al concluded that DCD recipients at high‐volume DCD centers had superior survival and decreased waitlist time compared to those at centers with lower DCD volume 15 . Our study provides a natural extension to these findings by demonstrating two key points.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…A recent analysis using UNOS data from 2011 to 2019 by Delman et al concluded that DCD recipients at high‐volume DCD centers had superior survival and decreased waitlist time compared to those at centers with lower DCD volume 15 . Our study provides a natural extension to these findings by demonstrating two key points.…”
Section: Discussionsupporting
confidence: 63%
“…A recent analysis using UNOS data from 2011 to 2019 by Delman et al concluded that DCD recipients at high-volume DCD centers had superior survival and decreased waitlist time compared to those at centers with lower DCD volume. 15 Our study provides a natural extension to these findings by demonstrating two key points. First, we show that increased DCD use benefits not only DCD recipients but also DBD recipients, though reduced waiting time, waitlist mortality and lower…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, establishing a new LT centre would require considerable expense and specialist staffing 6. Furthermore, there is an association with low volume LT centres and adverse patient survival so a minimum number of transplants per annum would need to be guaranteed 8 9…”
Section: Introductionmentioning
confidence: 99%